Generation of realistic synthetic catchments to explore fine continental surface processes. Issue 3 (11th January 2021) - Bunel, Raphaël; Lecoq, Nicolas; Copard, Yoann; Guérin, Eric; Van de Wiel, Marco; Massei, Nicolas
Abstract: Understanding, analysing, and predicting the erosion mechanisms and sedimentary flows produced by catchments plays a key role in environmental conservation and restoration management and policies. Numerical case‐testing studies are generally undertaken to analyse the sensitivity of flood and soil erosion processes to the physical characteristics of catchments. Most analyses are conducted on simple virtual catchments with physical characteristics that, unlike real catchments, are perfectly controlled. Virtual catchments generally correspond to V‐shaped valley catchments. However, although these catchments are suitable for methodical analysis of the results, they do not provide a realistic representation of the spatial structures of the landscape and field conditions. They can, therefore, lead to potential modelling errors and can make it difficult to extend or generalize their results. Our proposed method bridges the gap between real and traditional virtual catchments by creating realistic virtual catchments with perfectly controllable physical characteristics. Our approach represents a real alternative to traditional test case procedures and provides a new framework for geomorphological and hydrological communities. It combines a field procedural generation approach, geographic information system processing procedures, and the CAESAR‐Lisflood landscape evolution model. We illustrate how each of these components acts in the process of generating virtual catchments. Five physical parameters were adjusted and tested for each virtual catchment: drainage density, hypsometric integral, mean slope of the main channel, granulometry, and land use. One of our virtual catchments is compared with a real catchment and a virtual catchment produced by a standard method. This comparison indicates that our approach can produce more realistic virtual catchments than those produced by more traditional methods, while a high degree of controllability is maintained. This new method of generating virtual catchments therefore offers significant research potential to identify the impacts of the physical characteristics of catchments on hydro‐sedimentary dynamics and responses. Abstract : Most numerical case‐testing studies are conducted on simple V‐shaped valley catchments. However, although these catchments are suitable for methodical analysis of the results, they do not provide a realistic representation of field conditions. Our proposed method bridges the gap between real and traditional virtual catchments by creating realistic virtual catchments with perfectly controllable physical parameters: drainage density, hypsometric integral, mean slope of the main channel, granulometry, and land use.